(untitled) (Journal of Shaheed Suhrawardy Medical College, 2025)
Background: Vitamin D deficiency has been increasingly implicated in the pathogenesis of hypertension through its regulatory effects on the renin–angiotensin system and vascular endothelial function. Objectives: This study aimed to evaluate the impact of high-dose vitamin D supplementation on blood pressure control in hypertensive individuals with concurrent vitamin D deficiency. Methods: A randomized, double-blind, placebo-controlled clinical trial was conducted at Holy Family Medical College and Hospital, Dhaka, from January 2022 to January 2023. A total of 48 adult hypertensive patients with vitamin D deficiency (serum 25(OH)D <30 ng/ml) were enrolled and randomly assigned to either the Vitamin D Group (VDG, n=24) or Placebo Group (PG, n=24). The VDG received 50,000 IU of oral cholecalciferol weekly for 8 weeks, while the PG received a matching placebo. Baseline and post-intervention measurements included systolic (SBP), diastolic (DBP), and mean arterial pressure (MAP), along with serum 25(OH)D, parathormone, calcium, and electrolytes. Results: After 8 weeks, VDG showed significant reductions in SBP (−7.2 mmHg), DBP (−3.6 mmHg), and MAP (−4.8 mmHg) compared to negligible changes in the PG. Serum 25(OH)D levels increased substantially in VDG (+33.5 ng/ml vs. +2.0 ng/ml in PG), with normalization observed in 95.8% of VDG participants. Parathormone levels decreased significantly in VDG (−21.4 pg/ml), accompanied by a modest rise in serum calcium. No adverse effects were reported, and compliance was high in both groups. Conclusion: High-dose weekly vitamin D supplementation effectively improved vitamin D status and contributed to significant reductions in blood pressure among deficient hypertensive patients. These findings support the use of vitamin D as a safe and beneficial adjunct therapy for hypertension management in vitamin D-deficient populations. J Shaheed Suhrawardy Med Coll 2024; 16(1): 52-57